在△ABC中,求证:(a+b)^2*sin^2(C/2)+(a-b)^2*cos^2(C/2)=c^2 这题把我算晕了,把步骤写清楚了.

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/21 08:18:31
在△ABC中,求证:(a+b)^2*sin^2(C/2)+(a-b)^2*cos^2(C/2)=c^2 这题把我算晕了,把步骤写清楚了.
x){:gţiXlcӋHNҌ3*̋3p7H %Cl^rьg]]:&>_7̩Ovk\ig;Z-ճI*ҧv6^i~O5eCs k5UmH2`l!"@p`3(1JLBEF f.PP3D2jdz9 O'=tϲf=~O'D@o$فt

在△ABC中,求证:(a+b)^2*sin^2(C/2)+(a-b)^2*cos^2(C/2)=c^2 这题把我算晕了,把步骤写清楚了.
在△ABC中,求证:(a+b)^2*sin^2(C/2)+(a-b)^2*cos^2(C/2)=c^2 这题把我算晕了,把步骤写清楚了.

在△ABC中,求证:(a+b)^2*sin^2(C/2)+(a-b)^2*cos^2(C/2)=c^2 这题把我算晕了,把步骤写清楚了.
左边=(a+b)²sin²(C/2)+(a-b)²cos²(C/2)
=a²(sin²C/2+cos²C/2)+b²(sin²C/2+cos²C/2)+2ab(sin²C/2-cos²C/2)
=a²+b²-2abcosC
=c²(最后一步是余弦定理)
=右边